Does the US Tax Code Encourage Market Concentration? An Empirical Analysis of the Effect of the Corporate Tax Structure on Profit Shares and Shareholder Payouts - Sandy Brian Hager; Joseph Baines (Roosevelt Institute, 2023)
EXECUTIVE SUMMARY *** Concerns about the market power of large corporations are growing. There are good reasons why monopoly now features so prominently on the political and economic agenda. Mounting evidence shows that corporate concentration stifles innovation and investment, resulting in lower-quality goods and services and less economic dynamism. Concentration is also a catalyst for rising wealth and income inequality, as monopolistic firms are able to suppress workers' wages and charge consumers higher prices. *** Most of the public policy debate has been focused on the role of antitrust law in combating the monopolistic practices of large corporations. But recently, the focus has shifted somewhat, as more and more people come to recognize the role of federal and state-level taxation in understanding corporate concentration in the US. Yet, there are still many questions about the effect of taxation on market structure: Is there a tax advantage associated with bigness, as measured by revenues? If so, is this advantage confined to a few “bad apples” or is it widespread among large corporations? What role do the domestic and foreign tax systems play in encouraging monopoly power? What does an analysis of the relationship between tax and monopoly tell us about wider macroeconomic shifts in the US economy over the past few decades? *** The purpose of this brief is to address these questions by analyzing and comparing the overall effects of the US tax code on the profit share of large and smaller corporations. *** Our analysis reveals a striking tax advantage for big business in the US. Specifically, we find that the total post-tax profit share of the top 10 percent of listed corporations since the mid-1980s is consistently and significantly higher than their total pre-tax profit share, indicating that the overall tax structure (domestic and foreign) fuels profit concentration at the top of the corporate hierarchy. For example, in the most recent period covered in our analysis, 2019–2022, the overall tax structure has boosted the post-tax profit share of large corporations by 2.32 percentage points relative to their pre-tax share. We then assess the contribution of different tax jurisdictions to concentration by estimating the pre-tax and post-tax profit shares of large corporations, domestically and internationally. Here, our analysis reveals that the domestic tax structure is especially influential in driving concentration. Over the past four decades, the domestic post-tax profits of large corporations have been much larger than their pre-tax share, with the domestic tax structure augmenting the profit share of large corporations by 3.79 percentage points in 2019–2022. The effect of the foreign tax structure on profit concentration is more ambiguous. In most periods it is either slightly positive or slightly negative. For 2019–2022, the foreign post-tax profit share of large corporations was 0.87 percentage points higher than their pre-tax share. Based on these findings, we argue that the tax structure, especially the domestic tax structure, plays a crucial but still underappreciated role in exacerbating the monopoly problem. *** We go on to consider the wider consequences for the US economy of big business's tax advantage. The political justification for corporate tax cuts—including those that were part of the Tax Cuts and Jobs Act (TCJA) of 2017—is that they would free up money for companies to invest in productive capacity, in turn generating higher employment and wages. But as our analysis shows, the capital expenditures of large corporations tend to decrease, not increase, when their tax advantage grows. Instead of fueling productive investment, the tax savings of large corporations are principally used to pay out dividends and buy back their own stock. This means that large corporations are less disposed to investments that may indirectly benefit ordinary workers and more disposed to shareholder value enhancement that directly benefits the asset-rich. Overall, we find that the tax system contributes in crucial ways to rising corporate concentration and to widening inequality among households. *** With the objective of leveling the playing field, our findings offer powerful justification for the restoration of graduated statutory corporate income tax rates in the US alongside a global minimum effective tax rate of 25 percent and a graduated excise tax on share buybacks. The monopoly problem has become endemic to US capitalism, and corporate tax reform on its own will not solve it. Yet one clear advantage of taxation is that it has a direct, and therefore much more easily discernible, effect on distributive outcomes compared to other policy measures. A more holistic approach, combining corporate tax reform with more robust antitrust regulation, the strengthening of workers' rights, and increased public ownership in key sectors, is needed to build an economy based on equity, fairness, and prosperity for all.
Keywords: P; P1; P12; H2; H23; D4; D43; L; L11; M; 330; big business; centralization; concentration; corporation; distribution; dominant capital; production; inequality; power; profit; shareholders; tax; United States